TRANSLATION METHODS IN TRANSLATING IDIOMATIC WORDS FROM ENGLISH INTO INDONESIAN FILM SUBTITILES - Bena Yusuf Pelawi (Universitas Nasional, 2018)
This study aims to describe the role of translation methods in translating idiomatic words from English into Indonesian. The research is focussing on the idiomatic words in English film subtitles into the Indonesian version. It employed qualitative descriptive method. The data sources were English film subtitles “Eurotrip” directed by Jeff Schaffer and its translation in Indonesian version. The data analysis was content analysis using interactive model consisting of data reduction, data display, and conclusion drawing. The findings are as follows. First, there are 92 items of idioms found in the film subtitles, namely substitute (7), proper namen (42), abbreviation (4), English phrasal compound (7), figures of speech (11), and slang (21). Second, the translator employs four translation methods, there are literal (36), faithful (24), semantic (13) and communicative (19). Third, the translator tends to employ methods oriented to source language and culture. In general, the orientation to the source language and culture can result in a translation which is accurate, acceptable, and highly readable.